Experimental investigations on the effect of infill patterns on PLA for structural applications. (2023) - Akhil, V.M.; Aravind, S.L.; Kiran, Ravi; S P, Sivapirakasam; Mohan, Sreejith
Abstract: 3D printing is widely employed for a variety of applications due to its numerous advantages. The mechanical properties of a part made using 3D printing are quite important. As a result, it's critical to comprehend how distinct 3D printing process parameter values affect the part's mechanical qualities. However, for some applications, there needs a rigid framework that can tolerate parametric conditions. The mechanical strength of printed objects is influenced by printing parameters such as infill patterns, infill density, and print speed. The infill pattern of 3D printed material for exoskeleton application is examined in this study. In the study performed, it is attempted to find out the best infill pattern for good tensile and bending properties for a particular application. Out of the different patterns which are subjected to study in this investigation, it was found that, the maximum flexural stress value for a honeycomb type infill structure is 65 MPa but their tensile load capacity is less. Cubic type infill structure shows a highest flexural stress value of 64.8 MPa and tensile value of 20.56 MPa. Cubic type infill pattern gave the better result than other type of infill patterns which are subjected to different mechanical property evaluation in this study. According to the mechanical property investigation results obtained for the Cubic type infill pattern, it is found that, this type of infill pattern will be most suitable for exoskeleton applications.